A Tungsten Heavy Alloy with Enhanced Performance Prepared by Spark Plasma Sintering from Fine Spherical Tungsten Powders. Issue 5 (28th July 2022) - Hu, Ke; Han, Cuiliu; Khanlari, Khashayar; Zhang, Yumeng; Peng, Xiaomin; Zhang, Jiuxing
Abstract : Traditional tungsten heavy alloys (WHAs), with a coarse liquid‐phase sintered microstructure, have moderate strength and excellent ductility. Grain refinement is one of the effective methods to improve the strength of these WHAs. The routine spark plasma sintering (SPS) method can refine W grains; however, the obtained typical solid‐state sintered microstructure is detrimental to the performance. Adapted SPS methods such as cyclic SPS and transient liquid‐phase SPS, proposed in the previous study, are capable of modifying W grain morphology to further enhance the performance of parts. They are, however, complex processes, especially when it comes to mass production. In this research, 93W–5.6Ni–1.4Fe heavy alloys (93WHAs) with similar liquid‐phase sintered microstructure are prepared via SPS at solid‐state sintering temperature using fine spherical W powders as raw materials. The influences of the W powder shape and powder mixing condition on the microstructural and mechanical properties of the prepared 93WHAs are investigated. An improved microstructure is obtained in the 93WHA prepared using spherical W powders blended with nano Ni and Fe powders as raw materials, as compared to using the irregular W powders. The alloy thus shows elevated mechanical properties, due to the improved matrix phase distribution and the W grain morphology. Abstract : Herein, 93W–5.6Ni–1.4Fe heavy alloys with similar liquid‐phase sintered microstructure are prepared at solid‐state sintering temperature, by using spherical W powders as raw material and employing a one‐step spark plasma sintering method. The alloys show elevated mechanical properties, due to the improved matrix phase distribution (i.e., W–W contiguity) and the W grain morphology.